Prescribing Pattern and Rational use of Drugs in Maysan Governorate, Iraq - Haydar F. Al-Tukmagi; Abdul Rasool M.Wayyes (College of Pharmacy University of Baghdad, 2017)
This study was designed to investing the drug prescribing pattern which is the important point in the rational or irrational use of drugs among patients dispensing their prescriptions from the private pharmacies in Maysan governorate, Iraq for a period of 1 month. The data collected from prescriptions were calculated and analyzed according to the WHO prescribing guidelines. The data showed that the mean of drugs included in single prescription was 3.4, and 12% of prescribed drugs were written as generic names; moreover, the percentage of antibiotics, corticosteroids and anxiolytics were 33.3%, 11.4% and 23.8% respectively. Those results indicate the irrational use of drugs when compared with the world health organization standard values of prescribing indicators, in addition to the bad prescribing pattern regardless of the degree of specialization of the physician, where 52% of those prescriptions (analyzed in the present study) written by specialized physicians. In conclusion, actual intervention and follow up, training on rational use of drugs and intervention strategies for prescribers is required to improve the rational use of drugs. Key words: prescription pattern, polypharmacy, rational drug use